FAKTOR-FAKTOR YANG MEMENGARUHI NEUROPATI PERIFER TERKAIT HIV DI MANADO - Deivy Cirayow; Arthur Hendrik Philips Mawuntu; Herlyani Khosama (PERDOSNI, 2018)
FACTORS THAT INFLUENCE HIV ASSOCIATED PERIPHERAL NEUROPATHY IN MANADOABSTRACTIntroduction: There are several sociodemographic and clinical factors that influence the development of HIV associated peripheral neuropathy (HIV-PN). Manado has different sociodemographic and clinical characteristics from other regions. However, the percentage of HIV-PN and its influencing factors are unknown.Aims: To know the percentage of HIV-PN and factors that influence this disorder in Manado.Methods: A crosssectional study conducted in HIV/AIDS clinic R.D. Kandou hospital Manado between November2016–January 2017. Neuropathy evaluation was performed using brief peripheral neuropathy screening (BPNS), neuropathic pain diagnostic questionnaire (DN4), and electroneurography. A Chi-square or Fisher exact test was done to analyze categorical variables, independent T or Mann-Whitney test was done for numerical variables, and linear regression was done in multivariate analysis.Results: 50 subjects were included, most were male (70%), and the mean age was 32.98 (±9.726) years, with HIV- NP percentage was 46%. Age >30 years old, low hemoglobin count, CD4, and low international HIV dementia scale (IHDS) significantly associated with HIV-NP. Working subjects were 13.6 times more likely to have HIV-PN.Discussion: HIV-PN prevalence was relatively high, influenced by age >30 years old an low hemoglobin, CD4, andIHDS. As a factor, working was escalating the likelihood of NP-HIV by 13.9 times.Keywords: HIV/AIDS, influencing factors, peripheral neuropathyABSTRAKPendahuluan: Neuropati perifer terkait human immunodeficiency virus/HIV (NP-HIV) dapat dipengaruhi oleh beberapa faktor klinis dan sosiodemografis. Manado mempunyai karakteristik yang berbeda dengan daerah lain, namun belum diketahui persentase NP-HIV dan faktor-faktor yang memengaruhinya.Tujuan: Mengetahui persentase NP-HIV dan faktor-faktor yang memengaruhinya di Manado.Metode: Penelitian potong lintang terhadap pasien HIV/AIDS di poliklinik HIV/AIDS RSUP Prof. dr. R.D. Kandou, Manado, pada November 2016–Januari 2017. Evaluasi neuropati dilakukan menggunakan brief peripheral neuropathy screening (BPNS), neuropathic pain diagnostic questionnaire (DN4), dan elektroneurografi. Digunakan uji Chi-square atau Fisher exact untuk menganalisis variabel kategorik, uji T independen atau Mann-Whitney untuk variabel numerik, dan regresi linear untuk analisis multivariat.Hasil: Didapatkan 50 subjek yang memenuhi kriteria penelitian dengan mayoritas laki-laki (70%), rerata usia32,98±9,726 tahun, dan mengalami NP-HIV sebanyak 46%. Usia >30 tahun, kadar hemoglobin, jumlah CD4, dan skor international HIV dementia scale (IHDS) yang rendah berhubungan secara bermakna dengan adanya NP-HIV. Adapun subjek yang bekerja berisiko 13,6 kali lebih besar mengalami NP-HIV.Diskusi: Didapatkan prevalensi NP-HIV yang cukup tinggi dengan dipengaruhi oleh usia >30 tahun serta kadar hemoglobin, CD4, dan skor IHDS yang rendah. Faktor bekerja juga meningkatkan kecenderungan 13,9 kali mengalami NP terkait HIV.Kata kunci: Faktor-faktor yang memengaruhi, HIV/AIDS, neuropati perifer